Development of an IoT-Based Device for Real-Time Detection of Soil NPK Nutrient Content to Optimize Soybean Yields - Doan Perdana; Ongko Cahyono; Suntoro Suntoro (Agrotechnology Research Journal, 2025)
The optimal growth of soybean plants is critically dependent on the availability of essential nutrients in the soil, particularly nitrogen (N), phosphorus (P), and potassium (K). Plants achieve optimal growth when nutrient levels exceed deficiency thresholds. A significant challenge in soybean cultivation at the farmer level is the precise determination of fertilizer dosage and timing of application. This study presents an Internet of Things (IoT)-based device for the real-time detection of NPK nutrient content in soil, aimed at enhancing soybean yields. The device enables timely and accurate nutrient application, minimizing the soil's residual fertilizer risk, which can lead to environmental pollution and decreased land productivity. Field experiments were conducted to evaluate NPK fertilization methods on soybean crops in two distinct soil types, namely Vertisol and Entisol. The methodology involved comparing local farmers' fertilization practices with the recommendations derived from the NPK detection device. Results illustrated a significant increase in soybean yields when fertilization was performed according to the device's recommendations, yielding an increase from 1.2 to 1.79 t.ha-1 on Vertisol soil and from 1.75 to 2.57 t.ha-1 on Entisol soil.